Arktická strategie EU: Otázka aktérství Evropské unie - Slezáček, Filip (Univerzita Karlova, Fakulta sociálních věd, 2019)
Diplomová práce se zabývá určováním aktérství Evropské unie v rámci mezinárodního prostoru, který je v tomto případě omezen na Arktickou oblast. Politiky uvnitř EU nejsou stejnoměrně rozvinuté, a proto v určitých situací v určitém kontextu nemusí být EU považována za aktéra. Dokument Arktická strategie vyjmenovává tři pilíře - oblasti, v nichž by se EU měla snažit plnit své vytyčené cíle. Pomocí metody určování aktérství od Bretherton, C. et Vogler, J. se objasní, který pilíř je jak silný a jestli EU zvládá pozici aktéra ve světle svých cílů. This Master Thesis is depicting process of establishing actorness of the EU within international space, that is limited for this research on area of the Arctic. Policies of the EU are not uniformly developed, some are stronger, and some are weaker, that is a reason why in certain moments or position could be EU considered a non-actor. Document of Arctic Strategy is presenting system of three pillars- spheres in which the EU will be fulfilling its goals. Using the actorness assessment method by Bretherton, C. et Vogler, J. could be found out, how much a certain pillar is strong and whether the EU is able to fulfil its role as an actor in the light of its goals. Department of European Studies Katedra evropských studií Fakulta sociálních věd Faculty of Social Sciences